Pathology and Epidemiology of Cutaneous and Renal Glomerular Vasculopathy in Dogs. (April 2020) - Holm, L.P.; Stevens, K.B.; Walker, D.J.
Summary: Cutaneous and renal glomerular vasculopathy (CRGV) has been recognized as a potentially life-threatening condition of dogs in the UK since 2012, although there was a single (non-azotaemic) case reported in the UK in 2000. Prior to that, CRGV was recognized in the 1980s in southern USA as a disease affecting solely racing greyhounds (which gave rise to the colloquial name of 'Alabama rot'). CRGV manifests as ulcerative skin lesions, generally sparing the dorsum. It is variably associated with systemic signs including anaemia, thrombocytopenia and acute kidney injury, which, when it develops, is often severe and fatal. CRGV is characterized histopathologically as a thrombotic microangiopathy. To date in the UK, more than 230 dogs of varying breed and age have been humanely destroyed and histopathologically confirmed to be suffering from CRGV. The aetiology remains unknown, but the seasonal distribution (highest case incidence November–May each year) suggests that environmental or climatic factors may play a role in disease development. Further research to determine the aetiology and improve ante-mortem diagnostic testing, therapeutic options and preventive strategies is urgently needed.